Direct electrochemical reduction of carbon dioxide by a molybdenum-containing formate dehydrogenase - Cordas, Cristina M. (2019)
Formate dehydrogenase enzymes catalyse the reversible two-electron oxidation of formate to carbon dioxide. The class of metal-dependent formate dehydrogenases comprises prokaryotic enzymes holding redox-active centres and a catalytic site, containing either molybdenum or tungsten ion, that mediates the formate/carbon dioxide interconversion. The carbon dioxide reduction is of a particular interest, since it may be a route for its atmospheric mitigation with the simultaneous production of added-value products, as formate-derived compounds. Recently, the periplasmic formate dehydrogenase from Desulfovibrio desulfuricans, a molybdenum-containing enzyme, was proven to be an efficient enzyme for the CO 2 reduction to formate. In this work, the immobilized formate dehydrogenase isolated from Desulfovibrio desulfuricans direct electrochemical behaviour was attained in the presence and absence of substrates and the formal potentials associated with the catalytic centre transitions were determined in non-turnover conditions. The enzyme catalytic activity towards carbon dioxide reduction was observed using direct electrochemical methods.